2005
DOI: 10.1079/raf2005104
|View full text |Cite
|
Sign up to set email alerts
|

Chemical changes under aerobic composting and nutrient supplying potential of banana residue compost

Abstract: In anticipation of the Philippines being a major producer of organic bananas, this study was conducted to provide a quantitative basis for certain practices in organic farming. The nutrient supplying capacity of banana residues in combination with leguminous materials and chicken manure was investigated in composting studies. Changes in the chemical composition of ten formulations of banana residue-based compost involving leguminous plants (Sesbania rostrata, Flemingia macrophylla, Arachis hypogea) and chicken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…These results agreed with the findings of Kalemelawa et al [15], who observed the increase in P (86%) and K (34%) in banana peel with cow dung compost. Ultra et al [56] detected extremely large amounts of K, Ca Mg, and Na in banana waste compost. Moreover, the T 2 and T 3 composts resulted in extremely large amounts of Zn, Cu, and Mn through the humification of the added BPS and MMW.…”
Section: Changes In Nutrients Density During the Co-compostingmentioning
confidence: 99%
“…These results agreed with the findings of Kalemelawa et al [15], who observed the increase in P (86%) and K (34%) in banana peel with cow dung compost. Ultra et al [56] detected extremely large amounts of K, Ca Mg, and Na in banana waste compost. Moreover, the T 2 and T 3 composts resulted in extremely large amounts of Zn, Cu, and Mn through the humification of the added BPS and MMW.…”
Section: Changes In Nutrients Density During the Co-compostingmentioning
confidence: 99%
“…A neutral pH indicates that compost is mature and stable (Gobat et al 1998). This decrease can be explained by the release of organic acids with organic matter decomposition and/or CO 2 solubilization (Ultra et al 2005).…”
Section: Palm Compost and Manure Characterizationmentioning
confidence: 99%
“…Cavendish is also one of the most productive cultivars, characterized by productivity value of over 30 t/ha/yr. Banana plant is important not only as a food crop but is also used as a composting material [Ultra et al 2005], an energy source through decomposition [Clarke et al 2008], material for baskets, mats, tableware [Kambuou 2002], are required in social and religious rites in India [Mohapatra et al 2010].…”
Section: Introductionmentioning
confidence: 99%